ANALYSIS OF ENERGETIC INDICATORS OF FORESTRY MILLING MACHINES FOR SITE PREPARATION (Innovation in Woodworking Industry and Engineering design, 2026)
In this paper is performed experimental study to determine energy intensity of self-propelled milling unit PT-400 equipped with multifunctional forestry tiller FAE 300/S-225 for site preparation, for poplar plantation establishment. For the purpose of the study the following processes are investigated: grinding stumps and roots, mulching shrubs and slash, and primary tilling. The study is conducted in riparian and partially flooded areas along the Danube River. As a result of the survey are established the fuel consumption and the operational productivity of the forestry unit under certain working conditions and predefined variable modes of operation of the unit. For all the operations are found the energy intensity and the relative fuel consumption per unit area. With the obtained data are built functional graphical relationships, expressing the energy intensity of the milling unit depending on the speed modes and working conditions. As a final result are determined the optimal operational modes for the tilling aggregate where energy cost for land preparation for the establishment of poplar plantations is minimal.